Improved Survival Following Living Donor Liver Transplantation for Pediatric Acute Liver Failure: Analysis of 20 Years of US National Registry Data. Issue 8 (23rd July 2019) - Firl, Daniel J.; Sasaki, Kazunari; McVey, John; Hupertz, Vera; Radhakrishnan, Kadakkal; Fujiki, Masato; Eghtesad, Bijan; Miller, Charles M.; Quintini, Cristiano; Hashimoto, Koji
Abstract : This study estimated the utility of technical variant grafts (TVGs), such as split/reduced liver transplantation (SRLT) and living donor liver transplantation (LDLT), in pediatric acute liver failure (PALF). PALF is a devastating condition portending a poor prognosis without liver transplantation (LT). Pediatric candidates have fewer suitable deceased donor liver transplantation (DDLT) donor organs, and the efficacy of TVG in this setting remains incompletely investigated. PALF patients from 1995 to 2015 (age <18 years) were identified using the Scientific Registry of Transplant Recipients (n = 2419). Cox proportional hazards model and Kaplan‐Meier curves were used to assess outcomes. Although wait‐list mortality decreased (19.1% to 9.7%) and successful transplantations increased (53.7% to 62.2%), patients <1 year of age had persistently higher wait‐list mortality rates (>20%) compared with other age groups ( P < 0.001). TVGs accounted for only 25.7% of LT for PALF. In the adjusted model for wait‐list mortality, among other factors, increased age (subhazard ratio [SHR], 0.97 per year; P = 0.020) and access to TVG were associated with decreased risk (SHR, 0.37; P < 0.0001). LDLT recipients had shorter median waiting times compared with DDLT (LDLT versus DDLT versus SRLT, 3 versus 4 versus 5 days, respectively; P = 0.017). In the adjusted model for post‐LT survival, LDLT was superior to DDLT using whole grafts (SHR, 0.41; P = 0.004). However, patient survival after SRLT was not statistically different from DDLT (SHR, 0.75; P = 0.165). In conclusion, despite clear advantages to reduce wait‐list mortality, TVGs have been underutilized in PALF. Early access to TVG, especially from LDLT, should be sought to further improve outcomes.